Identification and NMR-based structural characterization of the functional domain of EPC3, a virulence effector of the phytopathogenic fungus Colletotrichum orbiculare - Xu, Zhe; Singkaravanit-Ogawa, Suthitar; Takano, Yoshitaka; Ohki, Shinya (Frontiers in Plant Science, 2025)
Plant pathogens secrete various effector proteins to induce infections in their host plants. Understanding the molecular basis of plant pathogen effectors is important for improving agricultural productivity, plant health, and sustainability. However, this remains a significant challenge. EPC3 (EPC; Effector Protein for Cucurbit infection) is a recently discovered effector involved in the virulence of the cucurbit anthracnose fungus Colletotrichum orbiculare on host plants, although the structure-function relationship is unknown. Here, we report that the N-terminal half domain of EPC3 is responsible for its function. We determined the solution nuclear magnetic resonance (NMR) structure and dynamic properties of this functional domain. The structure containing three disulfide (SS) bonds is composed of five β-strands. The molecule was rigid except for the loop regions connecting β-strands. The structural properties were compared with those of other structurally similar effectors to deduce the potential residues responsible for this function. Furthermore, mutation experiments demonstrated the importance of intramolecular disulfide bonds in maintaining the structural integrity of EPC3. Our results provided insights into the molecular characteristics of EPC3 and a basis for future structure-guided functional studies.